A conceptual framework to structure remote learning scenarios: a digital wall as a reflective tool for students to develop mathematics problem-solving competencies. (22nd June 2022) - Santos-Trigo, Manuel; Reyes-Martínez, Isaid; Gómez-Arciga, Adrián
The home confinement that was imposed to reduce and control the spread of COVID-19 pandemic led educational systems to implement changes in many school activities. Teachers moved to remote teaching and relied on digital apps to present and discuss learning activities with their students. Likewise, they looked for new routes and means to follow up and assess the students' achievement and problem-solving competencies. What is important in structuring an online teaching environment to foster students' learning of mathematics? To address this question, we present and discuss essentials of a conceptual framework to structure online learning environments. It includes three intertwined elements: a problem-solving approach for learners to learn mathematics, the students' use of digital affordances to represent, explore, and solve problems, and an online students' learning support. To this end, the use of a digital wall emerges as a reflective tool for students to organise, structure, and monitor their own learning experiences and problem-solving approaches.